USE OF PEDAGOGICAL TECHNOLOGIES ON LESSON OF RUSSIAN DURING WORK WITH ARTISTIC TEXT (ON MATERIAL OF STORY OF A. P.CHEKHOV «FIANCEE») - Olesja Gromakova; Tatiana Penina (Вестник Северо-Кавказского федерального университета)
To this article the example of the use of institution of higher learning technologies (in particular, lingostylistic aspect) is driven during work with text on the lesson of Russian; the certain system of language means (mainly verbs and nouns) that organize artistic time in the story of A. P. Chekhov «Fiancee»; their correlation is underlined with the basic theme of work. The special attention is spared to the functions of verbal forms, transmitter a temporal orientation from the past - in a present and - in the future. A standard over of reasoning is brought during work with text.